Efek Antibakteri Ekstrak Daun Mangrove (Acanthus Ilicifolius) Dengan Tiga Jenis Pelarut Terhadap Bakteri Enterococcus Faecalis(In Vitro) - Aryadi Subrata; Melisa Putri Usboko (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Irrigation is a stage to completely clean root canals when RCT is carried out to prevent recurrent infections. Increased antibiotic resistance and the side effects of using chemical irrigation solutions have led to the search for alternative herbal ingredients. Mangrove leaves (Acanthus ilicifolius) are known to contain bioactive compounds that can be effective antibacterial agents against gram-positive bacteria. Objective: To determine the differences in the antibacterial effect of Acanthus ilicifolius mangrove leaf extract with methanol, ethyl acetate and aquades solvents against Enterococcus faecalis bacteria. Methods: The leaves of Acanthus ilicifolius were extracted with maceration method using methanol (polar), ethyl acetate (semi-polar) and aquades (non-polar) and then diluted in concentrations of 1.56%, 3.13%, 6.25%, 12,5%, and 25%, chlorhexidine 2% as positive control and aquades as negative control. The extract effectiveness test was carried out with dilution method by mixing bacteria and extract each 20µl into 96 well-plate wells then incubated for 24 hours, followed by the diffusion method by inoculating as much as 5µl of the dilution results on a plate containing agar medium, then incubated for 24 hours. The number of bacterial colonies was then counted manually. Results: The extract had an antibacterial effect against Enterococcus faecalis, seen from a decrease in the number of bacterial colonies compared to negative controls, but not better than positive controls. The extract with the lowest number of colonies was found with a 25% concentration of methanol solvent. Data analysis was performed using the Kruskal Wallis test. Conclusion: There is no significant difference in antibacterial effect between the extract with the three different solvents. The extract with a concentration of 25% methanol as a solvent could not replace 2% chlorhexidine.